The economics of managing crop diversity on-farm: Case studies from the genetic resources policy initiative - Wale, E.; Drucker, Adam G.; Zander, K.K. (Routledge, 2011)
This book assesses a variety of economic issues as they relate to agro-biodiversity and shows how addressing these issues can assist in agro-biodiversity policy-making. This is illustrated using empirical data from some of the countries (Ethiopia, Nepal and Zambia) which are part of the Genetic Resources Policy Initiative.